Changes in the Prevalence of Natural Paramphistomum Cercariae Infection in Indoplanorbis and Lymnaea Intermediate Hosts Influenced by Meteorological Factors. (3rd February 2022) - Rafiq, Naseem; Ayaz, Sultan; Niaz, Sadaf; Haleem, Sumbal; Ullah, Riaz; Bari, Ahmed; Bourhia, Mohammed; Ali, Essam A.
Abstract : Paramphistomosis is a neglected ruminant parasitic disease caused by trematodes known as Paramphistomum, which has a diheteroxenic life cycle involving freshwater snail genera, i.e., Planorbis and Lymnaea as the intermediate host and mammals as the definitive host. Snail vector distribution, infection with Paramphistomum spp. cercariae, preferred habitat, and their relationship with certain meteorological factors were not investigated in the province Khyber Pakhtunkhwa of Pakistan. Therefore, this study is designed to evaluate the effects of meteorological factors on the occurrence and severity of Paramphistomum spp. cercariae in Indoplanorbis and Lymnaea intermediate snail hosts. For this purpose, a cross-sectional survey was conducted from October 2018 to September 2019, and snails were collected and then identified using snail shell morphology; their infection with Paramphistomum spp. cercariae was determined through microscopy; and descriptive statistics were used to estimate the prevalence of infection and evaluate their occurrence relationship with a certain meteorological factors including temperature, humidity, rainfall, and pan evaporation in different districts of the above-mentioned province of Pakistan, i.e., adjacent areas of Bara and Kabul rivers in district Nowshehra, Kabul River (Sardaryab) of district Charsadda, Kalpani River of district Mardan, and Indus River (Hund) of district Swabi. A total of 2, 706 Indoplanorbis (1539) and Lymnaea (1167) snails were collected, in which overall 10.30% shed Paramphistomum spp. cercariae. The highest infection rate was found in the river of district Swabi (13.20%), while the lowest in adjacent rivers of district Nowshehra (8.19%). Meteorological factors play an essential role in the causation of Paramphistomum spp. infection, parasitic reproduction, vector growth, and survival. Due to these factors, high significant prevalence was found in the summer season (11.83), followed by autumn (11.25), which might be due to optimum temperature, relative humidity, and rainfall (p < 0.05 ). It was concluded from the study that meteorological factors contribute to the prevalence of Paramphistomum species in the Indoplanorbis and Lymnaea, which act as vectors for the disease paramphistomosis, which may lead to the increased intensity of infection outbreaks of the parasite population in humans and domestic animals.